Resonators with tailored optical path by cascaded-mode conversions - Vincent Ginis; Ileana-Cristina Benea-Chelmus; Jinsheng Lu; Marco Piccardo; Federico Capasso (Nature Communications, 2023)
Resonators are key components in optics. In this work, the authors introduce a class of optical resonators with distinctly different properties from conventional resonators, allowing fundamental design trade-offs to be circumvented.